PENGARUH DESA DESENTRALISASI KEUANGAN TERHADAP KINERJA KEUANGAN DAN IMPLIKASINYA PADA AKUNTABILITAS MANAJEMEN KEUANGAN DESA - Prima Reza Wahyuni; Eni Duwita Sigalingging (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The aim of this research is to analyze the village's original income, savings and other resources, as well as the village's financial performance and village responsibilities in managing village finances. Sampling was purposive sampling of a population of 127 villages in Padang Pariaman district. The research sample consisted of 20 villages included in the